One-step introduction of the hexafluoroisobutyl group, synthesis of (S)-5,5,5,5',5',5'-hexafluoroleucine, and its incorporation into peptides and proteins - Delamare, Aline; Naulet, Guillaume; Mummadi, Sandeep; Guichard, Gilles; Compain, Guillaume (Comptes Rendus. Chimie, 2024)
The isobutyl motif is a highly prevalent functional group in medicinal chemistry, commonly present in numerous drugs and bioactive compounds. In biological systems, it notably corresponds to the side chain of the amino acid leucine. The replacement of this branched chain by the hexafluoroisobutyl group provides a significantly more hydrophobic moiety while maintaining a close global morphology. This modification has been overlooked due to the absence of general, simple, and/or efficient synthetic methods for introducing such a group into small molecules, amino acids, peptides, and proteins. In this account, we review our latest contributions to this field, highlighting the development of a general one-step method to incorporate the hexafluoroisobutyl group using a liquid fluorinated reagent. This method involves a tandem mechanism that overcomes the SN2' mechanism usually observed with α-(trifluoromethyl)vinyl groups. This methodology was successfully applied to the synthesis of (S)-5,5,5,5',5',5'-hexafluoroleucine (Hfl). Additionally, we summarize the research conducted on incorporating this valuable amino acid into peptides and proteins. Overall, this work opens new perspectives in organofluorine chemistry, medicinal chemistry, and protein engineering, which are also discussed herein.